THE EFL WRITING PROCESS DURING DISTANCE LEARNING: PROBLEM AND STRATEGY - Muhammad Zunizar Alfiansyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Within the final month of 2019, the world got negative wave named as covid19. It haschanged numerous things within the world. It is begun from human versatility, commerce, industry and etc. This phenomenon does not as it were alter whole of human social interaction, but moreover grant enormous changing of educational setting. After covid-19 cases raising up, the learning method became online course or distance learning method. The distance learning method which is still relatively new certainly has its own impact on the process. Because of that, the researcher conducted this study to find issues or learning challenges conjointly the procedures in composing 4 class during distance learning within the covid19 widespread period. The centering focuses investigated in this inquire about are the challenges or troubles that the understudies confront in composing 4 course, how the preferences of separate learning and the application of ICT in learning in terms of giving comfort or diminishing issues confronted by composing 4 course understudies. This research utilized qualitative strategy by portraying each result. The survey is the primary portion of this investigate. There are 28 questions within the frame of articulations given at the side the Likert scale as a way of replying. Afterward on, there was a meet session comprising of 11 questions. The 11 questions were tended to 4 members who were chosen from 50 members who had already gotten a survey before. The study found that the members did not have any critical issues with their composing handle. Typically demonstrated by the cruel esteem of the composing trouble variable which gets a unbiased or medium esteem. At that point, the application of the separate learning design taken after by the application of online-based learning which tends to person learning gets a beautiful great cruel score. At slightest the esteem is one step superior than the past variable. However, there are two points that got to be famous. The primary, the members feel exceptionally accommodating with online learning, but they still seem not make remove learning as the most strategy. Furthermore, the utilize of ICT for the members is as of now at a great level, but they still complain approximately the uneven accessibility of the internet in all places. So, the adaptability in remove learning is really not satisfied. As the conclusion, there are still numerous viewpoints that have to be made strides for getting superior quality in online learning.